Activin A induces skeletal muscle catabolism via p38β mitogen‐activated protein kinase. Issue 2 (16th September 2016) - Ding, Hui; Zhang, Guohua; Sin, Ka Wai Thomas; Liu, Zhelong; Lin, Ren‐Kuo; Li, Min; Li, Yi‐Ping
Abstract: Background: Activation of type IIB activin receptor (ActRIIB) in skeletal muscle leads to muscle atrophy because of increased muscle protein degradation. However, the intracellular signalling mechanism that mediates ActRIIB‐activated muscle catabolism is poorly defined. Methods: We investigated the role of p38β mitogen‐activated protein kinases (MAPK) in mediating ActRIIB ligand activin A‐activated muscle catabolic pathways in C2C12 myotubes and in mice with perturbation of this kinase pharmacologically and genetically. Results: Treatment of C2C12 myotubes with activin A or myostatin rapidly activated p38 MAPK and its effector C/EBPβ within 1 h. Paradoxically, Akt was activated at the same time through a p38 MAPK‐independent mechanism. These events were followed by up‐regulation of ubiquitin ligases atrogin1 (MAFbx) and UBR2 (E3α‐II), as well as increase in LC3‐II, a marker of autophagosome formation, leading to myofibrillar protein loss and myotube atrophy. The catabolic effects of activin A were abolished by p38α/β MAPK inhibitor SB202190. Using small interfering RNA‐mediated gene knockdown, we found that the catabolic activity of activin A was dependent on p38β MAPK specifically. Importantly, systemic administration of activin A to mice similarly activated the catabolic pathways in vivo, and this effect was blocked by SB202190. Further, activin A failed to activate the catabolic pathways in mice with muscle‐specific knockout of p38β MAPK. Interestingly, activin A up‐regulated MuRF1 in a p38 MAPK‐independent manner, and MuRF1 did not appear responsible for activin A‐induced myosin heavy chain loss and muscle atrophy. Conclusions: ActRIIB‐mediated activation of muscle catabolism is dependent on p38β MAPK‐activated signalling.